Effects of dietary lead exposure on vitamin levels in great tit nestlings – An experimental manipulation. (June 2016) - Ruiz, Sandra; Espín, Silvia; Rainio, Miia; Ruuskanen, Suvi; Salminen, Juha-Pekka; Lilley, Thomas M.; Eeva, Tapio
Abstract: Exposure to metal pollution negatively affects animal physiology, including nutrient metabolism, but in the wild an effect can seldom be attributed to a single metal. Moreover, little is known about how the metabolism of vitamins, essential micronutrients for developing juveniles, is affected by toxic metals. Therefore we experimentally investigated the effects of lead (Pb), a widespread toxic metal, on four fat-soluble vitamins A (total and retinol), D3, E (total and α-tocopherol) and K and carotenoids (lutein, zeaxanthin and unidentified) in great tit ( Parus major ) nestlings. In addition to a control group where no Pb was provided, two Pb-dosed groups were compared to a metal exposed group in the vicinity of a Ni–Cu smelter. We examined whether Pb treatment affects vitamin homeostasis and how the response of Pb-treated birds relates to that of a population under industrial exposure of Pb and other metals. For this purpose, vitamin and carotenoid levels were quantified with UPLC-MS from plasma of 7 days-old nestlings. All metal exposed groups showed increased vitamin A and retinol levels. However, vitamin levels were not directly associated with fecal Pb levels, with the exception of retinol, which was positively correlated with fecal Pb. Alpha-tocopherol, lutein and zeaxanthin levels were positively associated with body mass and wing growth rate. To conclude, Pb exposure increased plasma vitamin A and retinol levels while the levels of other vitamins and carotenoids rather reflected secondary pollution effects via differences in habitat and diet quality at the smelter site. Our findings suggest Pb exposed nestlings may allocate the vitamins needed for growth and development to fight the physiological stress thus compromising their fitness. Highlights: Pb effects on vitamins A, D3, E and K in wild great tit nestlings were investigated. Four treatment groups were established: Control, Low-Pb, High-Pb and Smelter. Pb concentrations measured in feces correlated positively with vitamin A (retinol). Pb treatment raised the concentration of vitamin A in plasma. Vitamin E (alpha-tocopherol) correlated positively with growth rates. Abstract : Pb exposure elevates plasma vitamin A levels in great tit nestlings.